2021
DOI: 10.3389/fnmol.2021.720220
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapies for Parkinsonian Syndromes–Recent Progress and Future Perspectives

Abstract: Background: Atypical parkinsonian syndromes are rare, fatal neurodegenerative diseases associated with abnormal protein accumulation in the brain. Examples of these syndromes include progressive supranuclear palsy, multiple system atrophy, and corticobasal degeneration. A common clinical feature in parkinsonism is a limited improvement with levodopa. So far, there are no disease-modifying treatments to address these conditions, and therapy is only limited to the alleviation of symptoms. Diagnosis is devastatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 225 publications
(286 reference statements)
0
16
0
Order By: Relevance
“…FtMt expression is induced by hydrogen peroxide treatment causing oxidative stress in the cells [ 19 ]. Oxidative stress is a harmful factor in the body and is associated with neurodegenerative diseases including AD, PSP, and PD [ 9 , 16 , 20 ]. Previous studies reported that patients with AD had an increased level of FtMt expression in the temporal cortex [ 19 ] and in the SNc of patients with PSP [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…FtMt expression is induced by hydrogen peroxide treatment causing oxidative stress in the cells [ 19 ]. Oxidative stress is a harmful factor in the body and is associated with neurodegenerative diseases including AD, PSP, and PD [ 9 , 16 , 20 ]. Previous studies reported that patients with AD had an increased level of FtMt expression in the temporal cortex [ 19 ] and in the SNc of patients with PSP [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3β may also be involved in neuronal apoptosis and mitochondrial activity ( Yang et al, 2017 ). Inhibition of GSK-3β was shown to protect dopaminergic neurons in various neurotoxic models of PD ( Petit-Paitel et al, 2009 ; Li et al, 2014 ) and is a target of ongoing drug development efforts ( Przewodowska et al, 2021 ). An analysis of crude extracts of Jurkat human T-cell leukemia clone E-6 cells revealed that incubation with PFF-A (and dieckol and eckol to lesser extent) inhibited GSK-3β activity ( Choi et al, 2015 ).…”
Section: Effects Of Phlorotannins Against Parkinson’s Diseasementioning
confidence: 99%
“…In addition, UA is an important natural antioxidant that demonstrates a relevant neuroprotective role in diseases related to oxidative stress. In fact, a low serum UA concentration has been associated with an increased risk of developing neurodegenerative diseases [48]. Thus, the efficient quantification of Do and UA is of great importance for human and animal health monitoring [49,50].…”
Section: Introductionmentioning
confidence: 99%